Desenvolvimento de um sistema de irrigação automatizado de baixo custo - Giomo, Diogo (2019)
Nowadays, irrigation is essential for the development of various agricultural crops. In many regions of the world, where in the past it was not possible to produce food due to the lack of rain, today irrigation has changed this scenario, providing cultivation throughout the year. However, many farmers lack the technical knowledge to manage this practice. Therefore, they irrigate empirically and thus damage the soil, crops and waste water and electricity. In view of the scarcity of water, it is essential that its use be made in a conscious and improved way. Along these lines, many automated irrigation systems help farmers to optimize the use of water in agricultural practices. However, these systems have high costs and are not viable for small farmers. Therefore, this work aims to develop a low-cost automatic irrigation system, allowing irrigation without human intervention, as well as data collection through a mobile application. In view of this, the sensors were calibrated and afterwards, a prototype was developed with three soil moisture sensors (in different positions), solenoid valve, Raspberry microcontroller and cloud computing. Thus, automation, in addition to managing irrigation, also collected data and stored it in an online service, thus making this information available for viewing through a mobile application via the internet. Consequently, the system achieved the objective of controlling irrigation, maintaining the soil moisture suitable for the chosen crop, with a final cost of R$ 290.81. This work was carried out with the support of the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (CAPES) - Código de Financiamento 001.